The BMI Paradox and Robotic Assisted Partial Nephrectomy - Kott, Ohad; Golijanin, Borivoj; Pereira, Jorge F.; Chambers, Alison; Knasin, Alison; Tucci, Christopher; Golijanin, Dragan (Frontiers in Surgery, 2020)
Introduction: Partial nephrectomy (PN), has become the gold standard for the surgical management of small renal masses, due to excellent oncologic control with concomitant preservation of nephron units. However, data regarding the association of obesity with perioperative outcomes following PN are mixed. Therefore, we sought to test the association between obesity (using BMI) and post-operative complications (PC) rate following Robotic assisted laparoscopic PN (RPNx). Methods: We identified 251 adult patients who underwent RPNx from 1/2011- 5/2017 at a single institution, with at least 90 days follow-up. Electronic medical records were reviewed to record all PC within 90 days of surgery. A piecewise generalized linear model for binary outcomes (logistic) was used to model the proportion of subjects with PC by their BMI. A piecewise approach allowed the slope of the line to adjust at the BMI of 30 Kg/m2. Results: BMI was found to be significantly associated with PC rate. PC rate decreased with increasing BMI below the inflection point of 30 Kg/m2 (0.848[0.756, 0.952]) (OR [95% CI], p=0.005). PC rate was found to increase with increasing BMI above the BMI inflection of 30 Kg/m2 (1.102 [1.027, 1.182], p=0.0071). Conclusions: In this cohort study, BMI showed an association with PC. It may be important to take BMI into account in surgical and clinical management considerations of RPNx, since we found it to be associated with higher rates of PC in patients who are underweight, morbidly obese and even with normal BMI. Further research is required on larger cohorts of RPNx patients to provide better description of this phenomenon.